Analisis Kesalahan Siswa Kelas XII dalam Menyelesaikan Soal Permutasi Berdasarkan Kriteria Watson melalui Model PBL Ditinjau dari Gender - Eka Finanti Septiana Simamora; Katrina Samosir (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to describe the types of students’ errors in solving permutation problems based on Watson’s criteria through the PBL model and to analyze differences in errors reviewed from a gender perspective. This study employed a descriptive quantitative approach with the subjects consisting of 30 students of class XII MATLANKO-2 at SMA Negeri 1 Percut Sei Tuan. Data were collected through essay tests and interviews, then analyzed by calculating final scores and the percentage of errors in each Watson category. The results showed that out of 102 identified errors, omitted conclusion errors and skill hierarchy problems each accounted for 25.49%, inappropriate procedures accounted for 15.68%, inappropriate data 14.70%, undirected manipulation 9.80%, and above other category 8.84%. Based on gender, male students were more dominant in skill hierarchy problems (28.89%) and above other category (20%), while female students were more dominant in inappropriate procedures (24.56%) and undirected manipulation (12.28%). The findings indicate that students’ errors were predominantly influenced by internal factors, particularly lack of conceptual understanding and weaknesses in procedural skills in solving permutation problems.